Visual and Quantitative Assessment of Coronary Stenoses at Angiography Versus Fractional Flow Reserve: The Impact of Risk Factors - Adjedj, Julien; Xaplanteris, Panagiotis; Toth, Gabor; Ferrara, Angela; Pellicano, Mariano; Ciccarelli, Giovanni; Floré, Vincent; Barbato, Emanuele; De Bruyne, Bernard (Circulation. Cardiovascular imaging, 2017)
The correlation between angiographic assessment of coronary stenoses and fractional flow reserve (FFR) is weak. Whether and how risk factors impact the diagnostic accuracy of angiography is unknown. We sought to evaluate the diagnostic accuracy of angiography by visual estimate and by quantitative coronary angiography when compared with FFR and evaluate the influence of risk factors (RF) on this accuracy. In 1382 coronary stenoses (1104 patients), percent diameter stenosis by visual estimation (DS ) and by quantitative coronary angiography (DS ) was compared with FFR. Patients were divided into 4 subgroups, according to the presence of RFs, and the relationship between DS , DS , and FFR was analyzed. Overall, DS was significantly higher than DS ( <0.0001); nonetheless, when examined by strata of DS, DS was significantly smaller than DS in mild stenoses, although the reverse held true for severe stenoses. Compared with FFR, a large scatter was observed for both DS and DS . When using a dichotomous FFR value of 0.80, C statistic was significantly higher for DS than for DS (0.712 versus 0.640, respectively; <0.001). C statistics for DS decreased progressively as RFs accumulated (0.776 for ≤1 RF, 0.750 for 2 RFs, 0.713 for 3 RFs and 0.627 for ≥4 RFs; =0.0053). In addition, in diabetics, the relationship between FFR and angiographic indices was particularly weak (C statistics: 0.524 for DS and 0.511 for DS ). Overall, DS has a better diagnostic accuracy than DS to predict the functional significance of coronary stenosis. The predictive accuracy of angiography is moderate in patients with ≤1 RFs, but weakens as RFs accumulate, especially in diabetics.